COMPARISON OF DATA CLUSTERING ALGORITHMS - Дорошенко, Ірина; Кнігніцька, Тетяна; Крештанович, Микита (SWorldJournal, 2024)
The article compares the comparison of data clustering algorithms: K-Means, Hierarchical Agglomerative Clustering (HAC), Density-Based Spatial Clustering of Applications with Noise (DBSCAN), Expectation–Maximization clustering using Gaussian Mixture Model